Shopping for Health: Whole Grains - Wendy J. Dahl; Lauren Foster (EDIS)
FSHN1013, a 4-page illustrated fact sheet by Wendy J. Dahl and Lauren Foster, describes the difference between whole grains and refined grains, how many grains we need, and how to shop for foods that contain whole grains. Includes references. Published by the UF Department of Food Science and Human Nutrition, November 2010.